2019
DOI: 10.3390/mi10070486
|View full text |Cite
|
Sign up to set email alerts
|

A Miniature Gas Sampling Interface with Open Microfluidic Channels: Characterization of Gas-to-Liquid Extraction Efficiency of Volatile Organic Compounds

Abstract: Chemosensory protein based olfactory biosensors are expected to play a significant role in next-generation volatile organic compound (VOC) detection systems due to their ultra-high sensitivity and selectivity. As these biosensors can perform most efficiently in aqueous environments, the detection systems need to incorporate a gas sampling interface for gas-to-liquid extraction. This interface should extract the VOCs from the gas phase with high efficiency and transfer them into the liquid containing biosensors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…The perireceptor events become an important source of inspiration for their sensitive and selective detection. [120] proposed an open channel microfluidic card for gas-to-liquid extraction. (d) The design proposed by Harun et al [121] helped to separate a sample spatially and temporally.…”
Section: Strategies Inspired By the Perireceptor Eventsmentioning
confidence: 99%
See 2 more Smart Citations
“…The perireceptor events become an important source of inspiration for their sensitive and selective detection. [120] proposed an open channel microfluidic card for gas-to-liquid extraction. (d) The design proposed by Harun et al [121] helped to separate a sample spatially and temporally.…”
Section: Strategies Inspired By the Perireceptor Eventsmentioning
confidence: 99%
“…(d) The design proposed by Harun et al [121] helped to separate a sample spatially and temporally. [120] proposed an open channel microfluidic card for gas-to-liquid extraction. (d) The design proposed by Harun et al [121] helped to separate a sample spatially and temporally.…”
Section: Strategies Inspired By the Perireceptor Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…A microfluidic gas-to-liquid (GTL) interface that uses an open capillary bed as a method of VOC capture has recently been developed [22]. The GTL interface dispersed 30 µL of a liquid capture agent throughout a microfluidic channel network.…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that decreasing the interface temperature to 15 • C during sampling and introducing a lipophilic binding agent such as α-cyclodextrin (α-CD) increased extraction efficiency for compounds with low water solubility. Under optimal conditions, the microfluidic GTL interface exhibited extraction efficiencies of 3.7% and 30% for allyl methyl sulfide and hexanal, respectively [22]. It is hypothesised that such a microfluidic device could be capable of extracting volatile ATS in gas samples.…”
Section: Introductionmentioning
confidence: 99%